2003
DOI: 10.1128/jvi.77.9.5487-5492.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Hepatitis C Virus RNA Replication Complex in Huh-7 Cells Harboring Subgenomic Replicons

Abstract: Formation of a membrane-associated replication complex, composed of viral proteins, replicating RNA, and altered cellular membranes, is a characteristic feature of plus-strand RNA viruses. Here, we demonstrate the presence of a specific membrane alteration, designated the membranous web, that contains hepatitis C virus (HCV) nonstructural proteins, as well as viral plus-strand RNA, in Huh-7 cells harboring autonomously replicating subgenomic HCV RNAs. Metabolic labeling with 5-bromouridine 5-triphosphate in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
541
1
7

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 564 publications
(588 citation statements)
references
References 34 publications
39
541
1
7
Order By: Relevance
“…Previously, we have shown that HCV RNA replication occurs on speckle-like structures [29], which may be equivalent to the membranous web, as reported by Gosert et al [45]. The immunofluorescence staining study presented here showed that PTB in Huh-7 cells mainly existed in the nucleus, while PTB in the replicon cells localized in not only the nucleus but also distinct structures in the cytoplasm and colocalized with the newly synthesized HCV RNA (Figure 1).…”
Section: Discussionsupporting
confidence: 86%
“…Previously, we have shown that HCV RNA replication occurs on speckle-like structures [29], which may be equivalent to the membranous web, as reported by Gosert et al [45]. The immunofluorescence staining study presented here showed that PTB in Huh-7 cells mainly existed in the nucleus, while PTB in the replicon cells localized in not only the nucleus but also distinct structures in the cytoplasm and colocalized with the newly synthesized HCV RNA (Figure 1).…”
Section: Discussionsupporting
confidence: 86%
“…(( Table 2) were found to be involved in lipid metabolism, membrane biogenesis, sorting and trafficking, supporting previous observations that HCV, like other positive-strand RNA viruses, replicates on altered host membranes, also described as "membranous webs" [68,69]. Furthermore, 6 genes were identified as being associated with the overlap between the results of these three screens and the study by Tai et al [65].…”
Section: Vsv-g-pseudotyped Particles Facilitate Virus Infection As VIsupporting
confidence: 81%
“…19,20,[27][28][29] It is largely unknown how NS4B interacts with other proteins. Recently, we have predicted a basic leucine zipper (bZIP) motif within the aminoterminal part of HCV NS4B.…”
Section: Discussionmentioning
confidence: 99%
“…13,18,19 The subcellular structure is considered to harbour the HCV replication complex, since all nonstructural proteins as well as viral genomic RNA were found to co-localize within this ER alterations. 19,20 The aminoterminal amphipathic a-helix (amino acid 1 to 26) has been described to mediate membrane association and correct localization of the replication complex within the ER. 7 Recently, Gouttenoire et al proposed the amphipathic a-helix to be located between amino acid 42 to 66.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation